2006
DOI: 10.1253/circj.70.1006
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of Uric Acid, Partly Secreted From the Failing Heart, is a Prognostic Marker in Patients With Congestive Heart Failure

Abstract: Methods PatientsStudy 1 Fifty consecutive patients with mild to severe CHF (left ventricular ejection fraction (LVEF) <45%, New York Heart Association (NYHA) functional classes II-IV) underwent diagnostic cardiac catheterization. Patients taking allopurinol, with renal failure, malignancy or congenital malformations of the heart or vessels were excluded. Renal failure was defined as an estimated glomerular filtration rate (eGFR) <30 ml · min -1 · (1.73 m 2 ) -1 according to the MDRD equation. 20 Informed conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
54
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 32 publications
5
54
0
2
Order By: Relevance
“…Considering that low LVEF was not associated with SUA in the full-adjusted model, association between SUA and elevated BNP may be, in part, attributed to the cardiac hypertrophy. 34) Another possibility is that uric acid secreted from failing heart may in part contribute to the increased SUA, 35) which might explain the observed association between SUA and BNP. On the other hand, however, the highest SUA was associated with elevated BNP, but not with LVH among female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that low LVEF was not associated with SUA in the full-adjusted model, association between SUA and elevated BNP may be, in part, attributed to the cardiac hypertrophy. 34) Another possibility is that uric acid secreted from failing heart may in part contribute to the increased SUA, 35) which might explain the observed association between SUA and BNP. On the other hand, however, the highest SUA was associated with elevated BNP, but not with LVH among female patients.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29][30] However, the prognostic role of the parameters of RAS such as renin, AngII and ALD remain controversial because many factors, including therapy for HF, influence the plasma levels of these markers. Plasma AngII concentrations have been reported as useful for predicting prognosis, despite ACEI therapy, 5,6 but in the present study it was not a prognostic predictor probably because of increased AngII after ARB therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38] Several studies have suggested that uric acid is a powerful prognostic factor in patients with cardiac failure and that uric acid may play a direct role in inducing myocardial damage. In the setting of AL, it is possible that uric acid is a surrogate marker for damage to additional organs, such as the kidney, potentially conferring additional prognostic value for this variable.…”
mentioning
confidence: 99%